Correlation between customer relationship management system usage, product innovation, and customer satisfaction - Wouroud Elfarmawi (Foundations of Management, 2019)
This quantitative correlational research examined the correlations between customer relation-ship management (CRM) usage, product innovation, and customer satisfaction. The general problem was the lack of evidence indicating the use of CRM system as effective in improving small- to medi-um-size companies' performance. Hence, the specific problem was to determine the beneficial use of a CRM system for customer satisfaction and product innovation. Data were gathered through sur-veymonkey.com. A total of 97 respondents were selected as sample from 10 small- to medium-size companies to answer the survey questions. Respondents were top managers, middle managers, and first-line managers of the selected organization. Statistics of the study were provided with the help of IBM Statistical Package for Social and Sciences version 23. The findings showed a strong correla-tion between the use of CRM system and customer satisfaction. They indicated the use of CRM system could improve the relationship with existing customers, could help attract prospective customers, and could win back former customers.
Keywords: M11; M15; O32; O33; 650; correlation design; CRM system; customer satisfaction; product innovation; quantitative re-search